An identification of defects at the academic building in UiTM Perak - Zaki, Izyani Athirah (2024)
An academic building is a facility used for educational and research purposes, such as classrooms, labs, libraries, and offices in schools or universities. Academic building defects are flaws in design, construction, or maintenance that affect the building’s safety, functionality, and usability. Academic building defects can significantly impact the learning environment, safety, and operational efficiency of educational institutions. This research aims to suggest the main solution of defect in academic buildings of UiTM Perak, a public university in Malaysia. The research will examine the types of defects, the causes and solutions of these defects, as well as the strategies for prevention and remediation. The study will also explore the impact of environmental factors, such as climate and soil conditions, on the development of construction flaws. The research employs a comprehensive approach, combining a thorough literature review and a detailed case study of the academic buildings at UiTM Perak. The literature review examines the existing body of knowledge on building defects, their types, causes, and impacts on educational settings. The case study involves on-site observation towards two selected buildings in UiTM Perak (QS building and Annex 1), interviews with facility managers, and analysis of maintenance records to gain a deep understanding of the specific defects present in the university's academic buildings. Remedial strategies and best practices to address the defects, including proactive maintenance programs, collaborative design and construction approaches, and the use of high-quality materials and techniques are purposed. The findings of this study provide valuable insights to enhance the safety, functionality, and sustainability of academic buildings.